Improvement Method of Antenna Negative Sidelobes on Cross Beam Correlation Microwave Radiometer - Xiaolong Feng; Hao Liu; Cheng Zhang; Donghao Han; Lijie Niu (Remote Sensing, 2024)
A weighting method is proposed for the correlation radiation measurement system based on Mills cross array. The Mills cross array achieves high spatial resolution by the product of two orthogonal fan beams. However, the product power pattern of the Mills cross array lacks a square operation, resulting in sidelobe deterioration and the presence of negative sidelobes. Therefore, a window function is necessary to improve beam performance. However, because of the negative sidelobes, the antenna array is sensitive to the weighting function, and common window functions such as Hanning and Hamming are not suitable for achieving optimal antenna performance. A weighting method is proposed to fully utilize the feature that the received energy of positive and negative sidelobes cancel each other out and to reduce the influence of antenna sidelobe errors in radiation measurement. Such a weighting function can be obtained by combining the combined cosine window function with the existing particle swarm optimization (PSO). The optimized window function is evaluated through numerical simulation and compared with the typical window function weighting results. The results show that this weighting method can minimize the impact of negative sidelobes and reduce the loss of spatial resolution.